Kelas Ibu Meningkatkan Pengetahuan dan Keterampilan Ibu di Desa Soliu - Stefanus Mendes Kiik; Muhammad Saleh Nuwa; Roslin E.M. Sormin (FORIKES, 2020)
The aim of this study was to investigate the effect of mother’s class on the knowledge and the skills among mothers in Soliu Village. This pre-experimental with one group pre- and post-test design used in this research. To collect data, purposive sampling was taken, involving 20 respondents. A paired t-test was used to compare group differences in the knowledge, and the skills. There were significant improvements in the knowledge (p